UJI KARAKTERISTIK CURAH HUJAN DAN DEBIT PENGALIRAN SUNGAI MAROS KAB. MAROS SULAWESI SELATAN - Amir, amir (Universitas Negeri Makassar, 2014)
ABSTRACTThis study aimed to test the characteristics of rainfall and river flow discharge in the river Maros Based on consideration of the safety factor in planning, then the selection of the data flow is taken so that the largest flood peak discharge values were selected based on the results of the analysis of rainfall of each which is considered to represent in the calculation. Â Increased erosion due to human activities upstream can affect the water level so that the value of the resulting discharge becomes smaller because of the sedimentation material deposition. The analysis is then used a variety of methods for precipitation method Normal Distribution (XT = X + k * Sd) and a Pearson Type III distribution method (X = X + k. Sd) and to the intensity of rainfall is the method Mononobe (I = 2/3 ) for the analysis of debits with synthetic hydrograph method method Nakayasu and Rational.Â Keywords : rainfall,debit,intensity, Maros riverÂ